A multi-staged approach to the reconstruction of a burnt Asian face - Janna Joethy; Bien-Keem Tan (Indian Journal of Plastic Surgery)
This article describes the management of chemical burns to the Asian face with resultant full thickness loss to the right side of the face including the eyelid and nose. We detail the techniques used to reconstruct the face which include skin grafting according to the aesthetic units of the face, accurate placement of junction lines, use of a chondrocutaneous graft to reconstruct the alar grove and scalp strip grafting for eyebrow reconstruction. We obtained a successful result that minimised scar formation in the burnt Asian face.